Visual Sociology Image Archives - Papademas, Diana; Kirkpatrick, Stephen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2011)
There seems to be no end to the images that can be found on the internet. Everyone should (and probably does) use Google Images (http://images.google.com). The following entries are some sites whose images, buried in databases, will not be harvested by Google but which are valuable, even though they are not in their original context. No doubt you will have your own favorites to add to these. The images are available for analysis but use of the images is usually governed by copyright law. Please use them properly.